1978
DOI: 10.1121/1.381808
|View full text |Cite
|
Sign up to set email alerts
|

Correlational study of speakers’ heights, weights, body surface areas, and speaking fundamental frequencies

Abstract: The purpose of this investigation was to determine the relationship among speakers' heights, weights, body surface areas, and speaking fundamental frequencies. The recordings of 30 speakers' readings of a standard prose passage were analyzed by means of the Fundamental Frequency Indicator (FFI) to obtain their speaking fundamental frequency characteristics. The speakers' heights and weights were obtained by means of standard measurement procuedures, and their body surface areas were calculated. Pearson product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 0 publications
2
60
0
1
Order By: Relevance
“…Larger male koalas were found to have lower formant frequency spacing, but no relationship between our proxy of male body size and F 0 was found. These findings accord with considerable research on other mammals, in which formant frequency spacing was found to be a reliable cue to male body size (Fitch, 1997;Riede and Fitch, 1999;Reby and McComb, 2003;Harris et al, 2006;Sanvito et al, 2007;Vannoni and McElligott, 2008;Charlton et al, 2009), whereas fundamental frequency is not (Lass and Brown, 1978;Masataka, 1994;Reby and McComb, 2003;Sanvito et al, 2007;Vannoni and McElligott, 2008). Whether koalas attend to size-related formant information in male bellows remains to be demonstrated.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Larger male koalas were found to have lower formant frequency spacing, but no relationship between our proxy of male body size and F 0 was found. These findings accord with considerable research on other mammals, in which formant frequency spacing was found to be a reliable cue to male body size (Fitch, 1997;Riede and Fitch, 1999;Reby and McComb, 2003;Harris et al, 2006;Sanvito et al, 2007;Vannoni and McElligott, 2008;Charlton et al, 2009), whereas fundamental frequency is not (Lass and Brown, 1978;Masataka, 1994;Reby and McComb, 2003;Sanvito et al, 2007;Vannoni and McElligott, 2008). Whether koalas attend to size-related formant information in male bellows remains to be demonstrated.…”
Section: Discussionsupporting
confidence: 71%
“…Consequently, if vocal fold length and/or mass are correlated to body size then F 0 could provide reliable information on the caller's size (Morton, 1977). However, while the prediction that larger animals should have lower F 0 is verified across age classes (Reby and McComb, 2003;Ey et al, 2007) and may hold across species of very different sizes (Hauser, 1993), F 0 is typically a poor cue to adult body size within a given mammalian species (Lass and Brown, 1978;Masataka, 1994;Reby and McComb, 2003;Rendall et al, 2005;Sanvito et al, 2007;Vannoni and McElligott, 2008). This lack of a correlation between F 0 and overall body size within species is less surprising when we consider that mammalian larynges are relatively unconfined by surrounding bony structures and can vary independently in size from the rest of the body (for a review, see Fitch and Hauser, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The weak relationship between F0 and body height is consistent with the absence of skeletal structures constraining the dimensions of the larynx, which results in vocal fold length being largely unrelated to overall body size (Fitch, 2000). Indeed, most acoustic studies have reported the absence of significant correlation between F0 and height within the sexes (Evans et al, 2006;González, 2004;Künzel, 1989;Lass, 1978;Rendall et al, 2005;Sawashima et al, 1983;Sell et al, 2010), though others have identified weak (β = −.16, Puts et al, 2012) to strong associations between the two variables (r = −.65 to −.71, Graddol and Swann, 1983). While the importance of F0 in cueing for speakers' actual size remains debated, psychoacoustic studies have consistently reported the perceptual salience of F0 in size ratings (Feinberg et al, 2005;Fitch, 1994;Pisanski and Rendall, 2011;Rendall et al, 2007;Smith and Patterson, 2005;Van Dommelen and Moxness, 1995), leading several authors to suggest that listeners may overgeneralise between-sex and age differences (Rendall et al, 2007), or broader sound-size associations in the natural world (i.e.…”
Section: Physiological Characteristics and Voice Cuesmentioning
confidence: 66%
“…By contrast, despite its dependence on the length, mass and tension of vocal folds (Titze 1994), in mammals the fundamental frequency of vocalizations does not consistently provide reliable information on body size (Lass & Brown 1978;Reby & McComb 2003a;Rendall et al 2005; but see Pfefferle & Fisher 2006). Nevertheless, F0 remains a highly distinctive and variable component of mammal calls and its covariation with caller attributes suggests that it might nonetheless provide important information for receivers in sexual contexts (e.g.…”
Section: Introductionmentioning
confidence: 99%